Dovgal A. G., Vronskaya O. S., Kostenko A. D. Development of gas-flame silicon carbide coatings with enhanced level of wear resistance. - Довгаль, А.Г.; Вронская, О.С.; Костенко, А.Д. (Problems of Tribology, 2014)
In order to improve the silicon carbide based coating some actions for reduction of their porosity and avoidance of chemical interaction with metallic binder have been investigated. For reduction of the porosity the wetting of the silicon carbide based ceramics by metallic melts has been studied. For avoidance of the chemical interaction of the silicon carbide with metallic melts the proper content of intermetallic phase has been chosen. Using the electron focus-beam microscopy, X-ray spectrometry analysis, X-ray phase analysis the interaction area of the ceramics and metallic melt have been researched. Having known the conditions of the ceramic metal composite acquisition the proper technique of coating deposition has been chosen. Thus the high velocity air fuel deposition technique due to its low temperature and smooth continuous action on the substrate has been chosen. On the ground of the contact interaction of the refractory component SiC-Al2O3 with the melts based on the nickel with the aluminium additives gas-flame silicon carbide coatings with the metallic bound have been developed. Using the electron focus-beam microscopy, X-ray spectrometry analysis, X-ray phase analysis the microstructure of these coatings acquired by the high velocity air fuel deposition has been researched. Tribotechnical properties of acquired coatings within the friction condition without lubricants on air have been studied. Using the electron focus-beam microscopy, X-ray spectrometry analysis, X-ray phase analysis the friction surface have been researched and features and regularities of their wear mechanisms have been detected.